1999
DOI: 10.1136/jnnp.67.1.109
|View full text |Cite
|
Sign up to set email alerts
|

Decreased cerebellar blood flow in postinfectious acute cerebellar ataxia

Abstract: Objective-The aim of the present study was to evaluate the regional cerebral blood flow (rCBF) in patients with postinfectious acute cerebellar ataxia using single photon emission computed tomography (SPECT). Methods-Five children with postinfectious acute cerebellar ataxia and five control subjects were examined. The distribution of rCBF was measured by SPECT imaging after intravenous administration of 123 I-IMP (111 MBq). The rCBF ratio-defined as the ratio of rCBF in the region of interest (ROI) to that in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…Acute cerebellar ataxia generally shows normal radiological findings on brain CT and MRI. However, a SPECT has demonstrated diminished perfusion of the cerebellum in patients with acute cerebellar ataxia, 9 as shown in our patient.…”
Section: Discussionsupporting
confidence: 72%
“…Acute cerebellar ataxia generally shows normal radiological findings on brain CT and MRI. However, a SPECT has demonstrated diminished perfusion of the cerebellum in patients with acute cerebellar ataxia, 9 as shown in our patient.…”
Section: Discussionsupporting
confidence: 72%
“…A few authors also reported on perfusion-SPECT in assessing cerebellar inflammation. Nagamitsu et al [27] stress the importance that cerebellar hypoperfusion (demonstrated with SPECT) is a more sensitive marker than MRI in AC. Their findings are based on five proven cases of AC.…”
Section: Discussionmentioning
confidence: 98%
“…Imaging plays a modest role in diagnosis; T2 signal change of the cerebellum is widely documented [60, 61] but structural MRI findings maybe normal if patients are imaged early in the course of the illness [62, 63]. While SPECT perfusion has been reported as a potential diagnostic biomarker in the course of the illness, reports vary with both increased and decreased perfusion demonstrated alongside normal MR appearances of the cerebellum [62, 63]. The pattern of cerebellar involvement is variable, though with the Purkinje cell a frequent immunological target in immune-mediated ataxia of which nature there is often a predominant cerebellar cortical volume as tends to be found in other immune ataxias [59].…”
Section: Section 5: Imaging In Immune-mediated Ataxiasmentioning
confidence: 99%